2018
DOI: 10.1002/adfm.201706995
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Chemical Flexibility and Nanoscale Charge Collection in Hybrid Halide Perovskites

Abstract: Hybrid organometal halide perovskites are known for their excellent optoelectronic functionality as well as their wide-ranging chemical flexibility. The composition of hybrid perovskite devices has trended toward increasing complexity as fine-tuned properties are pursued, including multielement mixing on the constituents A and B and halide sites. However, this tunability presents potential challenges for charge extraction in functional devices. Poor consistency and repeatability between devices may arise due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 192 publications
4
47
0
Order By: Relevance
“…[111][112][113] Heterogeneous distribution was found in the maps (Figure 13A), showing a molar ratio from 2.25 to 2.85, with average measured stoichiometry of 2.6 and standard deviation of 0.09; substoichiometry was observed, since a ratio of 3 was expected. [88] It was found that current collection increased as the molar ratio reached the stoichiometric value. Furthermore, when observing the XBIC current collection map a comparable heterogeneity is observed.…”
Section: Halide Heterogeneity and Stoichiometrymentioning
confidence: 99%
See 4 more Smart Citations
“…[111][112][113] Heterogeneous distribution was found in the maps (Figure 13A), showing a molar ratio from 2.25 to 2.85, with average measured stoichiometry of 2.6 and standard deviation of 0.09; substoichiometry was observed, since a ratio of 3 was expected. [88] It was found that current collection increased as the molar ratio reached the stoichiometric value. Furthermore, when observing the XBIC current collection map a comparable heterogeneity is observed.…”
Section: Halide Heterogeneity and Stoichiometrymentioning
confidence: 99%
“…Specifically, synchrotron-based XRF uses X-rays with 10 ppm sensitivity at a spatial resolution of 1 µm, [87] bulk penetration, while reducing the risk of sample damage or degradation. [80,88] These photons have a characteristic energy based on the element that was excited, therefore, it is the signal measured by the detector in the XRF instrument that will determine the constituent elements. [80] This way, a blast of energy is released which will be characteristic of a specific element.…”
Section: Micro-and Nano-x-ray Fluorescence (Xrf)mentioning
confidence: 99%
See 3 more Smart Citations